Continuous positive airway pressure effect on visual acuity in patients with type 2 diabetes and obstructive sleep apnoea: a multicentre randomised controlled trial. Issue 4 (25th October 2018) - West, Sophie D.; Prudon, Benjamin; Hughes, Joan; Gupta, Rajen; Mohammed, Seid B.; Gerry, Stephen; Stradling, John R.; ,
We sought to establish whether continuous positive airway pressure (CPAP) for obstructive sleep apnoea (OSA) in people with type 2 diabetes and diabetic macular oedema (DMO) improved visual acuity. We randomly assigned 131 eligible patients aged 30–85 years from 23 UK centres with significant DMO causing visual impairment (LogMAR letters identified ≥39 and ≤78, score 0.92–0.14) plus severe OSA on screening to either usual ophthalmology care (n=67) or usual ophthalmology care plus CPAP (n=64) for 12 months. Mean age of participants was 64 years, 73% male, mean body mass index 35.0 kg·m − 2 . Mean 4% oxygen desaturation index was 36 events·h −1 . There was no significant difference in the visual acuity at 12 months between the CPAP group and the control group (mean LogMAR 0.33 (95% CI 0.29–0.37) versus 0.31 (95% CI 0.27–0.35); p=0.39), and no significant correlation between change in LogMAR and average CPAP use. The median±sd (range) daily CPAP use was 3.33±2.25 (0–7.93) h at 3 months, 3.19±2.54 (0–8.07) h at 6 months and 3.21±2.70 (0–7.98) h at 12 months. CPAP therapy for OSA did not improve visual acuity in people with type 2 diabetes and DMO compared with usual care alone over 12 months. UK ROSA RCT shows 1 year of CPAP for OSA in people with type 2 diabetes and macular oedema does not improve visual acuity http://ow.ly/bw8H30lrAX8